2006
DOI: 10.1111/j.1365-2524.2006.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Expectations of support among White British and Asian-Indian older people in Britain: the interdependence of formal and informal spheres

Abstract: The discourse surrounding community care characterises informal support being superior to and preferred over formal sources of support, with this distinction buttressed by policy changes. There is a lack of understanding of the interdependence of both spheres of support. This article argues that an individual's experience and expectation of one type of support is often made in relation to his or her understanding, expectation and experience of other sources of support. There is also an urgent need to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…). Stigma and shame were found to arise in relation to ‘illness’ and to formal service use for some BME families (Sin ), as Victor et al . (: 90) note for carers from South Asian communities in the UK, ‘having to turn to the state for care was clearly construed extremely negative … indicating lack of family loyalty and potential loss of face within the wider community’.…”
Section: Limitations Of Mainstream Supportmentioning
confidence: 93%
See 4 more Smart Citations
“…). Stigma and shame were found to arise in relation to ‘illness’ and to formal service use for some BME families (Sin ), as Victor et al . (: 90) note for carers from South Asian communities in the UK, ‘having to turn to the state for care was clearly construed extremely negative … indicating lack of family loyalty and potential loss of face within the wider community’.…”
Section: Limitations Of Mainstream Supportmentioning
confidence: 93%
“…A consistent finding across all groups was a perception or fear of mainstream, traditional care and support as discriminatory. In his comparative study of the expectations of support among White British and Asian‐Indian older people in Britain, Sin (: 216) notes that, ‘a person's perception of the adequacy or quality of support is inevitably influenced by his or her expectations of the type, frequency and source of support preferred or required’. This was true for BME communities, LGB people, people from certain faith groups and asylum seekers and refugees, as the research studies suggested that all feared discrimination or misunderstanding, had low expectations of the suitability or accessibility of support and even feared interventions from large, generalist or mainstream providers (Price , ; Mir and Tovey ; Sin ; Yeung and Ng ; Cronin et al .…”
Section: Limitations Of Mainstream Supportmentioning
confidence: 99%
See 3 more Smart Citations